2020
DOI: 10.3390/genes11101203
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinesis-Block Micronucleus Cytome Assay Evolution into a More Comprehensive Method to Measure Chromosomal Instability

Abstract: This review describes the cytokinesis-block micronucleus (CBMN) cytome assay and its evolution into a molecular cytogenetic method of chromosomal instability (CIN). Micronuclei (MNi) originate from whole chromosomes or chromosome fragments that fail to segregate to the poles of the cell during mitosis. These lagging chromosomes are excluded from the daughter nuclei and are enveloped in their own membrane to form MNi. The CBMN assay was developed to allow MNi to be scored exclusively in once-divided binucleated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 66 publications
1
53
0
5
Order By: Relevance
“…We also observed that exposure to the both EDCs was able to impact the NDI of HepG2 cells and previous studies showed that oxidative damage in DNA is related to cell cycle arrest (Droge, 2002;Murray and Carr, 2018). Reduced NDI is associated with more mononucleated cells, when compared to bi-, tri-, and polynucleated ones, giving evidence of cell cycle arrest (Fenech, 2007(Fenech, , 2020. Interestingly, the most pronounced effects on NDI were seen when the cells were treated with the combinations of TCS and DEHP, at all doses.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We also observed that exposure to the both EDCs was able to impact the NDI of HepG2 cells and previous studies showed that oxidative damage in DNA is related to cell cycle arrest (Droge, 2002;Murray and Carr, 2018). Reduced NDI is associated with more mononucleated cells, when compared to bi-, tri-, and polynucleated ones, giving evidence of cell cycle arrest (Fenech, 2007(Fenech, , 2020. Interestingly, the most pronounced effects on NDI were seen when the cells were treated with the combinations of TCS and DEHP, at all doses.…”
Section: Discussionsupporting
confidence: 75%
“…In this context, MNs may also arise through gene amplification through fusion bridge breaking (BFB) cycles. In the case of NBUDs, DNA is selectively located at specific locations on the periphery of the nucleus and can be eliminated through nuclear sprouting, during S phase of the cell cycle; then, as consequence, extrusion of amplified DNA via nuclear sprouting may result in MN formations (Fenech and Crott, 2002;Mateuca et al, 2006;Fenech, 2020). It is also important to mention that we did not observed increase of NPBs in cells treated with TCS and DEHP.…”
Section: Discussionmentioning
confidence: 51%
“…We found no significant difference in NB formation between the exposed workers and controls (Table 3). This could be expected, considering how NBs as indicators of genetic instability are formed (94)(95)(96). They are the consequence of elimination of amplified genes and unresolved DNA repair complexes (94).…”
Section: Resultsmentioning
confidence: 96%
“…This could be expected, considering how NBs as indicators of genetic instability are formed ( 94 , 95 , 96 ). They are the consequence of elimination of amplified genes and unresolved DNA repair complexes ( 94 ). Inorganic lead did not activate any detoxification pathway or induce an over-expression of genes and consequently their copy number.…”
Section: Discussionmentioning
confidence: 93%
“…Harmonised assay protocols and scoring approaches have been detailed by Organisation for Economic Cooperation and Development (OECD)-Test Guideline 487 (OECD 2016). In addition to regulatory compound screening, the assay is also widely used for more specific research and clinical purposes including compound mode-of-action determinations, tumour radiosensitivity prediction and inter-individual monitoring of lifestyle, occupational and environmental factors including radiation biodosimetry assessments (Decordier and Kirsch-Volders 2006;Fenech 2000;Fenech 2020;Kirsch-Volders et al 2011;Wang et al 2019).…”
Section: Declarations Introductionmentioning
confidence: 99%